Analisis Manajemen Operasional Alat Pemecah Batu Pada Unit Pengolahan Batu Andesit di PT Calvary Abadi Klaten Jawa Tengah - Mokodompis, Oktavian (Program Studi Teknik Pertambangan, Fakultas Sains dan Teknik, Universitas Bangka Belitung, 2025)
Calvary Abadi is located in Somopuro Village, Jogonalan District, Klaten Regency. Crushing activity in andesite stone crusher units consists of three stages, namely primary crushing (jaw crusher I), secondary crushing (jaw crusher II) and tertiary crushing (jaw crusher III). Currently the crushing plant is only capable of producing broken andesite stones of 166,939 tons / day with a size (10-20) mm of 54,243 tons / day, (20-30) mm of 7,924 tons / day and (5-10) mm of 34,771 ton / day. And the calculation of production in April and May 2016 resulted in an average production of only 1,335.504 tons / month. Based on production scheduling, the production target set is 250 tons / day or 2500 tons / month with the desired material size, namely (10-20) mm of 85.0 tons / day, (20-30) mm of 85 , 0 tons / day and (5-10) mm by 80.0 tons / day. To achieve the desired production target, it is necessary to have a good and correct tool maintenance management by always optimizing every scheduled maintenance systematics. Systematics maintenance of the first tool is preventive maintenance. PT. Calvary Abadi is carried out by applying three systematic procedures for maintenance, namely pre-maintenance, daily maintenance and periodic maintenance and emergency maintenance. The systematic review of maintenance on prevention based on the calculation of the unresolved preventive maintenance analytical method is 7.14%, so that it is still categorized as safe because less than 10% of the maximum inspection is not resolved. And corrective maintenance based on calculation analysis is said to be stable because it is more than 80%, ie the percentage of capability is 89.3%.